Adsorption of dinitrogen tetroxide on activated carbon fabric derived from novolacs. Issue 10 (3rd October 2017) - Ursini, Ornella; Angelini, Giancarlo; Cataldo, Franco
ABSTRACT: Activated carbon fabric (ACF) obtained from novolacs carbonization was used as substrate for N2 O4 adsorption. In one case the ACF was soaked and impregnated with liquid N2 O4 (ACF-liq-N2 O4 ) reaching an adsorbate loading of about 1400 mg N2 O4 /g(ACF). Another ACF was prepared by adsorption of a gaseous stream of N2 O4 (ACF-gas-N2 O4 ). This time the adsorbate loading was found at 757 mg N2 O4 /g(ACF). The two samples were studied with FT-IR spectroscopy before and after the desorption. The amount of N2 O4 in the ACF samples was determined gravimetrically, thermogravimetrically (TGA) and by wet chemical analysis after hydrolysis of the samples in water. The N2 O4 /NO2 desorption from the ACF was studied by TGA-FTIR analytical technique and it was found that the NO2 desorption starts at low temperatures and reaches a peak at 158–170°C. In the correspondence of the NO2 release peak starts also the gasification of the oxygenated groups present in the ACF with a simultaneous peak in the emission of CO2 and CO. From the DSC analysis of ACF-liq-N2 O4 and ACF-gas-N2 O4 the heat of adsorption of N2 O4 was determined and found at –21.8 kcal/mol for ACF-liq-N2 O4 and –16.2 kcal/mol for ACF-gas-N2 O4 . The electrical resistivity of the ACF before and after the N2 O4 adsorption was measured.